The European Union explained : institutions, actors, global impact - Staab, Andreas, 1965- (Indiana University Press, 2011)
This brief and accessible introduction to the European Union is ideal for scholars and professionals in government, business, the media, or the nonprofit sector who need a concise overview of the structure, history, and policies of the EU. This new edition also provides useful background reading for advanced high school and college courses and for those planning overseas study, work, or research. Andreas Staab offers basic terms and interpretive frameworks for understanding the evolution of the EU; the ov.